Incidence and control of fascioliasis around Niono, central Mali - Traoré, A. (1989)
Determines fascioliasis incidence in domestic ruminants and ways of controlling the disease around Niono, central Mali. Includes data on liver fluke infestation rate, proportions of animals infested with liver flukes and having ruptured livers, and mortality due to acute fascioliasis.